I hate rules! - Krulik, Nancy E. (Krulik, Nancy E. Katie Kazoo, switcheroo, 2003)
Third-grader Katie Carew gets into trouble for breaking school rules, but when she magically turns into the school's principal and eliminates all rules, things get out of hand. Includes directions for playing Four Square, Statue Tag, and Poison.